Identification and Characterization of Fungi Associated with Leaf Spot Disease of Rubber Trees (Hevea brasiliensis) in Pahang, Malaysia - Nur Ain Izzati Mohd Zainudin; Nur’ain Azhar; Muhamad Najmi Haikal Rosli; Nor Aisyah Md Nordin (Jurnal Proteksi Tanaman)
Rubber trees are important sources of agricultural income as they are utilized for lumber and latex. Like other crops, they are susceptible to numerous fungal pathogens, especially on their leaves, the most important plant part. Therefore, this study was conducted to identify the fungi associated with leaf spot disease on the leaves of rubber trees. This study aimed to characterize fungi associated with diseased rubber leaves and determine the causative agent of leaf spot disease. A total of 20 fungal isolates were obtained and purified from rubber leaves collected during sampling in rubber plantations in Pahang, Malaysia. All the isolated fungi were identified as Colletotrichum siamense (2 isolates), Diaporthe sp. (5 isolates), Lasiodiplodia pseudotheobromae (1 isolate), L. theobromae (7 isolates) and Neoscytalidium sp. (5 isolates). Based on a pathogenicity test, it was found that nine isolates were pathogenic towards the leaves of rubber, which were L. theobromae, L. pseudotheobromae, and C. siamense. The lesions on the leaves displayed chlorosis with varying necrotic lesion sizes after 21 days post-inoculation. The isolates of the species L. theobromae were the most prevalent, indicating it is more widespread in the region than other species. The findings present data on the potential pathogen of rubber plants and are important to understand further the potential risks and effects of the pathogen in rubber plantations